Public-private partnerships and developing-country agriculture: Evidence from the international agricultural research system - Spielman, David J.; Hartwich, Frank; von Grebmer, Klaus (Wiley, 2010)
This study examines the role of public–private partnerships (PPPs) in promoting pro‐poor productivity‐enhancing technological innovation in the international agricultural research system. The study examines the extent to which PPPs are being used to overcome market and institutional failures that otherwise inhibit the development and dissemination of technologies targeted specifically to small‐scale, resource‐poor farmers in developing countries. Drawing on a survey of 75 PPP projects in the international system, findings suggest that while PPPs are changing the way the system manages its research agenda, few partnerships lead to joint innovation processes with the private sector. This indicates the need for closer examination of organizational practices, cultures, and incentives in the international agricultural research system. Copyright © 2010 John Wiley & Sons, Ltd.